A comparison between traditional and knowledge input output tables - Ronald B. Davies; Guohao Yang (University College Dublin, UCD School of Economics, 2024)
Input-Output tables have become the workhorse data structure when considering global supply chains since, by definition, they measure how production in one countrysector is linked to that in another via trade in intermediate inputs. What traditional input-output tables miss, however, is the role of knowledge. In this paper, we use the well-known World Input-Output Database and construct a corresponding "Knowledge" input-output dataset based on patenting information from PATSTAT. Thus, for 44 countries over 20 sectors for 15 years, we are able to compare linkages via intermediate goods to those created by patent citations. We illustrate that these two networks share strong similarities in terms of the size of activity and linkages yet important differences - most notably the interaction between Asia and the rest of the world - are found. We then conclude by illustrating the link between patents and a measure of intangible capital that can be constructed from the World Input-Output Database, a relation that is a function of tax haven status. This then suggests that there is a likely direct connection between the data found in the production data and those derived from the patent data.
Keywords: F12; O33; O34; R12; 330; Input Output Table; Innovation; Networks; Centrality; Tax Havens